Recognizing the Paradigm of the Unknowing Victim and the Implications of Liminality - Ost, Suzanne (The British journal of criminology, 2024)
This article presents the novel conceptualization of the unknowing victim (UV) and addresses the ethical ramifications of this status. Criminology and victimology have primarily focused on knowing victims, but certain crimes occur without the victim’s detection (e.g. sexual assault of an unconscious victim). There is a critical liminal dimension to UV’s status: they are on the threshold between unawareness and conscious awareness of their status as victims of crime and are thus situated on the brink of experiencing harm through their own discovery, or someone else’s disclosure, of the crime committed against them. We call for the recognition of UVs and the temporalities of their embodied experiences, and argue that there is an ethical imperative to prioritize their lived experience.